3.2k views
2 votes
Which algebraic expression is equivalent to the expression below?

3(5x + 7) – 6(4 – 2x)
270 - 3
27r - 12
12r + 3
12. + 27
ha

User Puemos
by
5.2k points

2 Answers

2 votes

Answer: 27x=3

Step-by-step explanation: 3(5x+7) -6(4-2x) = 3(5x+7) + (-6)(4+(-2x)) = 15x + 21 + (-24) + 12x =15x + 12x + (-24) + 21 =27x + (-3) =27x-3 hope this helps

User Amila Dulanjana
by
6.0k points
4 votes

Answer:


\boxed{27x - 3}

Explanation:


= > 3(5x + 7) - 6(4 - 2x) \\ \\ = > (3 * 5x) + (3 * 7) - (6 * 4) - (6 * ( - 2x)) \\ \\ = > 15x + 21 - 24 - ( - 12x) \\ \\ = > 15x - 3 + 12x \\ \\ = > 27x - 3

User Jamona Mican
by
5.5k points